2021
DOI: 10.3390/s21124048
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Dried Droplets for the Quality Control of Medicines

Abstract: The quality control of medicines guarantees the effectiveness of treatments for diseases. We explore the use of texture analysis of patterns in dried droplets as a tool to readily detect both impurities and changes in drug concentration. Four types of medicines associated with different routes of administration were analyzed: Methotrexate, Ciprofloxacin, Clonazepam, and Budesonide. We use NaCl and a hot substrate at 63 ∘C to promote aggregate formation and to reduce droplet drying time. Depending on the medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Third, variants prepared by means of the different mixing procedures share a great diversity of textures. Therefore, the use of traditional techniques such as gray level co-occurrence matrix (GLCM) 49 – 51 , and fractal-based measures 2 can lead to ambiguities in texture differentiation. We have observed that LCFD histograms of DEM patterns are not unique.…”
Section: Discussionmentioning
confidence: 99%
“…Third, variants prepared by means of the different mixing procedures share a great diversity of textures. Therefore, the use of traditional techniques such as gray level co-occurrence matrix (GLCM) 49 – 51 , and fractal-based measures 2 can lead to ambiguities in texture differentiation. We have observed that LCFD histograms of DEM patterns are not unique.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies demonstrated that NaCl induces the formation of complex aggregates in alcoholic drinks and medicines [ 56 , 59 ]. Our finding show that NaCl generates complex aggregates that allow one to classify and differentiate among deposit groups.…”
Section: Discussionmentioning
confidence: 99%
“…Entropy is defined from gray level co-occurence matrix. According to [ 56 , 57 ], we calculated the probability of variation between gray level i and j in a displacement distance ( d ) and angle ( ) with the matrix element given by: …”
Section: Methodsmentioning
confidence: 99%
“…It suppresses the recrystallization and the coffeering effect [176]. In terms of pharmaceutical applications, Carre´on et al [241] studied the quality of different medicinal drugs (methotrexate, ciprofloxacin, clonazepam, and budesonide) as a function of the initial concentration, added NaCl, and substrate temperature.…”
Section: B Current Challenges Of Bio-colloidal Drying Dropletsmentioning
confidence: 99%